Analyzing the Offense of Juvinile Khalwat in Aceh: Evaluation of Qanun Number 14 of 2003 from an Islamic Legal Perspective - Harahap, Zul Anwar Ajim; Zulfan,; Ridwan, Muhammad (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
Aceh presents an intriguing area of study for numerous researchers in legal domains, owing to its distinct legal system in contrast to other regions in Indonesia. This legal jurisdictional authority underscores the intricacies involved in delineating the jurisdictional boundaries within the overarching framework provided by the national regulations. This is evident in cases of khalwat, an offense where a man and a woman date in seclusion. This study delves into an examination of the offense of juvenile khalwat in Aceh, as stipulated in Qanun Number 14 of 2003, employing Islamic legal theory within a sociological context. The findings of this study suggest that the juvenile occurrence of khalwat in Aceh stems from a combination of factors. These include the enduring influence of religious teachings, the prevalence of casual relationships among adolescents coupled with insufficient parental supervision, and the impact of modern social structures on youthful behavior. As a result, they engage in the offense of khalwat in public spaces, disregarding societal moral norms and public decorum. This Qanun fails to explicitly delineate the parameters for imposing penalties such as ‘uqubat (corporal punishment), flogging, and fines. Consequently, it leads to legal disparities in enforcement by the Wilayatul Hisbah, particularly when the offender is a minor or immature individual.